A Systematical Review of Readiness For Change of Human and Organization Resources a Case study in Health Organization - Dyah Pikanthi Diwanti; Norhaziah Nawai (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2022)
The study aimed to determine the historical development of Readiness for Change Of Human Resources in Health Organizations from the initial findings to current developments and future readiness for change in human and organizational resources. The study administered a systematic review of approximately 100 journals on readiness for change human and organizational resources. The findings from the development of readiness for change human and organizational resources referred to a review of readiness for change human and organizational resources development from several points of view, including a review of factors that influence the readiness of changes in human resources and organizations both internally and externally in Health Organization. In addition, the change readiness assessment is to examine the level of readiness of conditions organizational commitment is a psychological attachment between an employee and his organization. Another external factor that affects readiness to face change is the psychological climate.